The effect of thermal aging on solid insulating materials: A case study for dielectric loss and dissipation factor based evaluations under different voltage levels and frequencies - Akin, Firat; Arikan, Oktay (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Investigating the dielectric performance phenomenon in insulating materials is critical for con-dition monitoring and early failure diagnosis. In this study, the effect of thermal aging on dielectric losses and dissipation factors of four insulating materials are investigated: PET, SBR/ NR, presspaper and HDPE. A series of measurements at 4 kV and 10 kV with eight different frequencies between 50 Hz and 400 Hz are used to determine the dielectric loss and dissipation factor values of the materials during aging process. Thus, the non-ideal structure of electrical networks and the presence of harmonics are considered. Referring to the results, it is found that the level and frequency of the applied voltage greatly affects the performance of the materials. Also, it is seen that thermal aging have a significant impact on the dielectric properties of the materials. Furthermore, thermal aging effect on the results of different frequencies differs ac-cording to the material type.
Keywords: Electrical engineering; Power system equipment; Solid insulating materials; Dielectric properties analysis; Thermal stress; Harmonics; Engineering; Materials Science